Household Food Consumption and Poverty Reduction After Earthquakes: Evidence from Lombok - Pratama, Amy Wardian; Sari, Dyah Wulan; Auwalin, Ilmawan (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This study contributes to the literature by examining how household food consumption mitigates the poverty impact of earthquakes, an area that remains underexplored in post-disaster economic studies.Research Objectives: The study aims to analyze the role of per capita household food consumption in poverty reduction after the Lombok earthquake and to highlight its importance for economic recovery.Research Methods: This study uses panel data from 10 districts/cities in West Nusa Tenggara (2011-2019) to employ the First-Difference Generalised Method of Moments (FDGMM) to address potential endogeneity and estimate the causal relationship between food consumption and poverty.Empirical Results: The results show that per capita food consumption significantly reduces poverty under normal conditions and after a disaster. Meanwhile, economic growth positively impacts poverty, suggesting that the observed growth is not inclusive. The study also finds that the direct effect of the earthquake on food consumption is statistically insignificant, suggesting that other factors, such as relief programs, may have played a role in stabilizing consumption.Implications: These findings underscore the importance of policies that enhance food security and equitable distribution, particularly in post-disaster contexts. Strengthening social protection programs and ensuring inclusive economic growth is essential for long-term poverty reduction in disaster-prone areas.JEL Classification: C33, I32, Q54How to Cite:Pratama, A. W., Sari, D. W., & Awwalin, I. (2025). Household Food Consumption and Poverty Reduction After Earthquakes: Evidence from Lombok. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 65-76. https://doi.org/10.15408/sjie.v14i1.43926.